Performance Of Forecasting Models In IT Projects - Nesterova, Anna (2019)
The main aim of the present document is to improve the predictive capabilities of project management by selecting suitable methods and integrating them into the reality of international IT project, where the level of uncertainty is very high. In this paper, the probabilistic forecasting model is compared with different types of deterministic forecasting models to prove that it has better forecasting performance. The first chapter is dedicated to forecasting activities in project management. The second chapter presents a theoretical overview of chosen methods and their theoretical comparison. In the last chapter forecasting performance of each model is analyzed based on real IT project, and then compared according to specified evaluation criteria.